Fiber Optic Sensors in Chemical and Biological Applications - Kuncová, Gabriela (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Special Issue "Fiber Optic Sensors in Chemical and Biological Applications" gathers recent original papers. The subjects of the papers cover a broad range of optical fiber chemical sensors and biosensors applied for regulation in bioreactors, to novel concepts of intrinsic optical fiber sensors.